The position of Lithuanian parties towards Poland in 1920-1926: from modus vivendi to permanent confrontation - Andrius Grodis (Lietuvos Istorijos Studijos)
In the end of the First World War, Lithuanian (having just regained independence) international position was badly complicated by a terror conflict with Poland with respect to Vilnius that took place in 1919. However, despite the hostility to Poland entrenched in society, the leaders of political parties who envisioned the greatest danger to the state's independence from Soviet Russia and Germany actively sought pacific means of resuming the historical capital of the state and for ways of friendly affiliation of interstate relations.